Quality of caesarean delivery services and documentation in first-line referral facilities in Afghanistan: a chart review - Kim Young-Mi; Tappis Hannah; Zainullah Partamin; Ansari Nasrat; Evans Cherrie; Bartlett Linda; Zaka Nabila; Zeck Willibald (BMC, 2012)
Abstract Background Increasing appropriate use and documentation of caesarean section (CS) has the potential to decrease maternal and perinatal mortality in settings with low CS rates. We analyzed data collected as part of a comprehensive needs assessment of emergency obstetric and newborn care (EmONC) facilities in Afghanistan to gain a greater understanding of the clinical indications, timeliness, and outcomes of CS deliveries. Methods Records were reviewed at 78 government health facilities expected to function as EmONC providers that were located in secure areas of the country. Information was collected on the three most recent CS deliveries in the preceding 12 months at facilities with at least one CS delivery in the preceding three months. After excluding 16 facilities with no recent CS deliveries, the sample includes 173 CS deliveries at 62 facilities. Results No CS deliveries were performed in the previous three months at 21% of facilities surveyed; all of these were lower-level facilities. Most CS deliveries (88%) were classified as emergencies, and only 12% were referrals from another facility. General anesthesia was used in 62% of cases, and spinal or epidural anesthesia in 34%. Only 28% of cases were managed with a partograph. Surgery began less than one hour after the decision for a CS delivery in just 30% of emergency cases. Among the 173 cases, 27 maternal deaths, 28 stillbirths, and 3 early neonatal deaths were documented. In cases of maternal and fetal death, the most common indications for CS delivery were placenta praevia or abruption and malpresentation. In 62% of maternal deaths, the fetus was stillborn or died shortly after birth. In 48% of stillbirths, the fetus had a normal heart rate at the last check. Information on partograph use was missing in 38% of cases, information on parity missing in 23% of cases and indications for cesareans missing in 9%. Conclusions Timely referral within and to EmONC facilities would decrease the proportion of CS deliveries that develop to emergency status. While the substantial mortality associated with CS in Afghanistan may be partly due to women coming late for obstetric care, efforts to increase the availability and utilization of CS must also focus on improving the quality of care to reduce mortality. Key goals should be encouraging use of partographs and improving decision-making and documentation around CS deliveries.